Prediksi Prevalensi Stunting di Indonesia dengan Ordinary Least Square (OLS) - Benny Putra; Alva Hendi Muhammad (Universitas Islam Raden Rahmat, Malang, 2024)
Stunting is a growth issue in children, a serious concern both in Indonesia and globally, affecting over 149 million children worldwide, including 6.3 million in Indonesia. Despite some reduction, achieving the national target by 2024 remains challenging. The government has issued a Presidential Regulation to address stunting, focusing on family nutrition and environmental hygiene. This study aims to predict stunting prevalence, develop a more accurate prediction model, provide a basis for policy, and contribute to the scientific literature on stunting in Indonesia. The methods used include comparing algorithms such as Neural Network (NN), RBF Network, SVR kernel RBF, and Ordinary Least Square (OLS). The evaluation shows significant performance variation: NN performs fairly well, RBF Network performs better, SVR kernel RBF also performs well, but OLS stands out with very accurate predictions, minimal error values, and high correlation.